Land Readiness Analysis for Tanah Kuning Port Based on Integrated Topographic Data - Edy Utomo; Muhammad Djaya Bakri; Daud Nawir; Muhammad Asfihan Nur Arifin; Iif Ahmad Syarif (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2026)
The coastal area of Tanah Kuning, Bulungan Regency, is planned as part of the development of the Tanah Kuning-Mangkupadi Industrial Estate and International Port (KIPI) in North Kalimantan Province. This study aims to analyze port land readiness based on topographic conditions to inform technical planning for port development. The study offers an approach to evaluating land readiness by integrating terrestrial surveying using a Total Station with aerial photogrammetry using a UAV drone. The data were processed into a Digital Terrain Model (DTM) and contour maps for slope and land elevation analysis. The assessment was conducted descriptively and evaluatively, in accordance with KP.227/DJPL/2019, taking into account slope conditions, protection against the highest high-water level, and existing land use. The results show that location 1 has the most stable conditions, with dominant slopes of 0-25%, elevations above the highest high-water level, and no active settlements. Therefore, it is classified as suitable. In contrast, Locations 2 and 3 are classified as unsuitable due to the dominance of steep to very steep slopes and socio-land constraints.